Repliche a una pretesa critica di Schatzman a Freud sul caso clinico del presidente Schreber. Contributi eziologici precipui della psicanalisi sulla paranoia (Parte seconda: construens) - Tosto, Maria Grazia (Metapsychologica - rivista di psicanalisi freudiana, 2024)
This article constitutes the second and final part of a study by the author devoted to a rereading of Sigmund Freud’s Psychoanalytic Notes ( Psychoanalytische Bemerkungen, 1910) on the clinical case of President Schreber. More precisely, in the function of pars construens, it intends to complete and conclude the argument undertaken in the first part (pars destruens), which appeared in the previous issue of this same journal, by following up the rebuttals made to Morton Schatzman’s purported critique of Freud (1973) with a more systematic identification of the strengths that make Freud’s examination not only paradigmatic for every later psychoanalytic study of paranoia, but also almost unimpeachable on the epistemological level, by virtue of a complex of prerogatives, including the following: 1) a selection and treatment of sources consistent with the specific nature of the object of psychoanalysis i.e. the subject; 2) an etiological investigation selected according to a functional and modern causal framework; 3) an evident methodological rigour, beginning with the consideration of the various avenues that can be pursued and the limitations as well as the advantages that each of them may present, and ending with the choice of the one most suitable for the specific case under consideration; 4) a proper focus, within a mare magnum of data, of the most versatile for a productive start of the study, identified in this particular case, in Schreber’s dreams, as the «royal road» to access the unconscious; 5) a predominantly heuristic development of the discourse, which proceeds through cogent questions and hypotheses, some accepted, some discarded; 6) a perfect and constant relationship of coherence and consistency between the theory on the one hand and the available empirical data set on the other. Finally, after moving on from clarifications which, as a stringent refutation of certain serious misinterpretations of the Freudian text, have occurred in the past, and have recently been authoritatively made on the Bemerkungen (see F. Baldini, Metapsychologica, 2019/1), the present article suggests a debate on some further hypotheses.